Double‐pulsed diffusional kurtosis imaging. (20th February 2014) - Jensen, Jens H.; Hui, Edward S.; Helpern, Joseph A.
<x xml:space="preserve">Abstract</x> Diffusional kurtosis imaging (DKI) is extended to double‐pulsed‐field‐gradient (d‐PFG) diffusion MRI sequences. This gives a practical approach for acquiring and analyzing d‐PFG data. In particular, the leading d‐PFG effects, beyond what conventional single‐pulsed field gradient (s‐PFG) provides, are interpreted in terms of the kurtosis for a diffusion displacement probability density function (dPDF) in a six‐dimensional (6D) space. The 6D diffusional kurtosis encodes the unique information provided by d‐PFG sequences up to second order in the b‐value. This observation leads to a compact expression for the signal magnitude, and it suggests novel data acquisition and analysis methods. Double‐pulsed DKI (DP‐DKI) is demonstrated for in vivo mouse brain with d‐PFG data obtained at 7 T. Copyright © 2014 John Wiley & Sons, Ltd.